2013
DOI: 10.1093/nar/gkt623
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epigenetic stability and conversions in Saccharomyces cerevisiae reveals a novel role of CAF-I in position-effect variegation

Abstract: Position-effect variegation (PEV) phenotypes are characterized by the robust multigenerational repression of a gene located at a certain locus (often called gene silencing) and occasional conversions to fully active state. Consequently, the active state then persists with occasional conversions to the repressed state. These effects are mediated by the establishment and maintenance of heterochromatin or euchromatin structures, respectively. In this study, we have addressed an important but often neglected aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 74 publications
6
37
0
Order By: Relevance
“…In the absence of CAF-I these chromatin conversions are impeded and the cells remain in 2C-like state. Such an interpretation is in agreement with the proposed role of CAF-I as a regulator of epigenetic conversions 8 and can be supported by the findings in. 4,5 A very important implication of this interpretation is that CAF-I is generally involved epigenetic conversions in eukaryotic cells.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…In the absence of CAF-I these chromatin conversions are impeded and the cells remain in 2C-like state. Such an interpretation is in agreement with the proposed role of CAF-I as a regulator of epigenetic conversions 8 and can be supported by the findings in. 4,5 A very important implication of this interpretation is that CAF-I is generally involved epigenetic conversions in eukaryotic cells.…”
supporting
confidence: 90%
“…10,11 However, a recent study has pointed out that the loss of telomeric gene silencing in Dcac1 cells should be attributed to low frequency of conversions between the active and silenced states rather than to overall reduced silencing. 8 Hence, this paper suggested that in S.cerevisiae CAF-I is involved in epigenetic conversions.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…28 These assays showed the all S!A mutants reduced the repression of a telomeric URA3 reporter 2-to 9-fold relative to wild type cells ( Fig. 7) with S503A and S94A showing the weakest and strongest effect, respectively.…”
Section: Mutations Of the Serines Targeted By Cdk And Ddk Reduce Telomentioning
confidence: 89%
“…The deletion of CAC1 is known to cause sensitivity to DNA damaging agents, 7,27 loss of telomeric gene silencing, 4,5 decrease in the frequency of epigenetic conversions at telomeres 28 and impaired in vitro replication-coupled nucleosome assembly. 5,29 However, point mutations in Cac1p that affect its interaction with PCNA do not phenocopy the loss of CAC1.…”
Section: Mutations Of the Serines Targeted By Cdk And Ddk Reduce Telomentioning
confidence: 99%